Improving Students' Reading Comprehension by Using Reciprocal Teaching at SMP YADIKA 2 Tegal Alur, Jakarta Barat - Hutasoit, Mawar S (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2017)
The main objective of this research was to find out whether students' reading comprehension improved when taught using reciprocal teaching. The research method was classroom action research. The subject of this research was the 35 students of class VIII B at SMP YADIKA 2, consisted of 6 males and 29 females students. The qualitative data obtained from an interview, observation, and researcher's diary notes, while the quantitative data obtained from the pretest and posttest. The result indicated that there was an improvement in students' reading comprehension. It can be seen from the mean score of the students (Pretest: 60.21; posttest cycle 1: 74.42; and posttest cycle 2: 86.78). In addition, from the interview result, the researcher found that the students enjoyed learning reading using reciprocal teaching. The conclusion of the research is that reciprocal teaching technique can improve the students' reading comprehension. It is suggested that teachers should apply reciprocal teaching as a teaching technique in the classroom. Keywords: classroom action research, reading comprehension, reciprocal teaching.